Direct methanol fuel cell bifunctional catalyst and preparation method thereof
A bifunctional catalyst with nitrogen-doped tungsten carbide and platinum-nickel alloy nanochains addresses the slow kinetics of MOR and ORR in direct methanol fuel cells, improving performance and resistance to CO poisoning, thus enhancing the efficiency of direct methanol fuel cells.
Patent Information
- Application Number
- CN202411276313.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The slow kinetics of the anode methanol oxidation reaction (MOR) and cathode oxygen reduction reaction (ORR) in direct methanol fuel cells hinder their commercial application, and the 'mixed potential' from methanol penetration reduces the open circuit voltage and efficiency, with platinum-based catalysts being costly and susceptible to CO poisoning.
A bifunctional catalyst is developed using carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays and platinum-nickel alloy nanochains, with a preparation process involving PECVD treatments and hydrothermal synthesis to enhance conductivity and active sites, improving MOR and ORR performance.
The catalyst exhibits high conductivity, specific surface area, and resistance to CO poisoning, significantly enhancing the MOR and ORR performance, making it suitable for direct methanol fuel cells.
Smart Images

Figure CN119170817A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of direct methanol fuel cell catalysts, and in particular relates to a direct methanol fuel cell bifunctional catalyst and a preparation method thereof. Background Art
[0002] With the rapid advancement of population growth and industrialization, especially the rapid consumption of non-renewable resources such as coal and oil after the Industrial Revolution, data show that global energy demand has increased significantly in the last century and is expected to increase by nearly 48% in the next 20 years to meet the needs of sustainable industrialization and human population. Direct methanol fuel cells (DMFCs) have gradually come into people's view due to their high energy density, low operating temperature and good portability. They have become one of the most promising electrochemical energy conversion devices and are used in fields that require portable energy, such as automobiles, aerospace, and trucks. However, the slow kinetics of the anode methanol oxidation reaction (MOR) and the cathode oxygen reduction reaction (ORR) seriously hinder the commercial application of DMFC. In addition, the "mixed potential" generated by methanol penetration reduces the open circuit voltage and efficiency of the battery, and the actual DMFC power output is lower than the theoretical value.
[0003] Currently, precious metal catalysts, especially platinum-based catalysts, are the most commonly used materials for ORR and MOR. However, due to the high cost, scarcity and susceptibility to CO poisoning of platinum itself, the development of efficient bifunctional catalysts for direct methanol fuel cells is key. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a direct methanol fuel cell bifunctional catalyst and a preparation method thereof, which has the characteristics of high conductivity, high specific surface area and good electrochemical performance.
[0005] The first aspect of the present invention provides a direct methanol fuel cell bifunctional catalyst, using carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays as a conductive substrate, and platinum-nickel alloy nanochains wound on the high-conductivity tungsten carbide substrate.
[0006] The second aspect of the present invention provides a method for preparing a bifunctional catalyst for a direct methanol fuel cell, comprising the following steps:
[0007] (1) preparing carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays;
[0008] (2) Surface treatment of carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays by PECVD;
[0009] (3) Synthesis of Pt-Ni alloy polyhedral nanochains by hydrothermal reaction;
[0010] (4) The Pt-Ni alloy polyhedron nanochain synthesized in step 3 is loaded on the carbon cloth of the nitrogen-doped tungsten carbide nanoarray treated in step 2 by self-adsorption to obtain a platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material;
[0011] (5) calcining the platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material obtained in step 4 in air, nitrogen and argon-hydrogen successively and then annealing to obtain a carbon cloth surface loaded with nitrogen-doped tungsten carbide nanoarrays and loaded with a Pt-Ni alloy polyhedron nanochain catalyst;
[0012] (6) A second PECVD treatment is performed to obtain a Pt-Ni alloy polyhedral nanochain catalyst loaded on the surface of a nitrogen-doped tungsten carbide array modified by Ar / NH3 plasma, which is a bifunctional catalyst for direct methanol fuel cells.
[0013] Furthermore, the treatment temperature of the second PECVD treatment in step 6 is 100-300°C.
[0014] Furthermore, step 6 includes: cooling the carbon cloth surface loaded with nitrogen-doped tungsten carbide nanoarray obtained in step 5 and then subjecting it to a second PECVD treatment, the atmosphere is argon ammonia, the gas flow rate is 30Pa, the plasma discharge RF power is 75W, the duration is 60min, the treatment temperature is 200°C, and after cooling, Ar / NH3 plasma modified nitrogen-doped tungsten carbide array surface loaded with Pt-Ni alloy polyhedron nanochain catalyst is obtained, recorded as P-PtNi@PN-WC@CC.
[0015] Furthermore, step 1 includes: dissolving tungstic acid powder in hydrogen peroxide, heating at 90-100°C for 2.5-3.5h, then adding HCl and Na2SO4 to dissolve, placing carbon therein and heating at 170-180°C for 11-13h to obtain a WO3 nanoarray, then adding melamine and heating at 800-900°C under argon for 2.5-3.5h for carbonization to obtain a nitrogen-doped tungsten carbide array.
[0016] Furthermore, step 2 includes: performing room temperature plasma enhanced chemical vapor deposition on the substrate in an Ar / NH3 atmosphere, with a gas flow rate of 18-22Pa and a plasma discharge RF power supply power of 95-105W for 50-70min.
[0017] Furthermore, step 3 includes: mixing a platinum source, a nickel source, hexadecyltrimethylammonium chloride, glucose and oleylamine, ultrasonically treating the mixture at room temperature to form a uniformly distributed mixed solution, then heating from room temperature to 170-190°C and maintaining at this temperature for 11-13 hours to complete the reaction, naturally cooling the product to room temperature, collecting the product by centrifugation and washing with ethanol to obtain a Pt-Ni alloy polyhedron nanochain.
[0018] Preferably, the platinum source is platinum acetylacetonate, the nickel source is nickel acetylacetonate, and the molar ratio of platinum acetylacetonate to nickel acetylacetonate is 2:1.
[0019] Furthermore, step 4 includes: placing the nitrogen-doped tungsten carbide array surface treated in step 2 into cyclohexane, magnetically stirring, ultrasonically dispersing the Pt-Ni alloy polyhedron nanochain prepared in step 3 in another portion of cyclohexane, and then mixing the above two solutions, and then magnetically stirring and dispersing and adsorbing for 12 hours to obtain a platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material.
[0020] Furthermore, step 5 includes: the platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material obtained in step 4 is heated from room temperature to 180°C in air within 20 minutes, and kept warm for 1 hour; nitrogen is introduced and kept warm for 2 hours; and then the temperature is raised to 400°C at a rate of 7 to 8°C / min in an argon-hydrogen atmosphere, and kept warm for 4 hours to obtain a carbon cloth surface loaded with nitrogen-doped tungsten carbide nanoarrays. The catalyst is loaded with a Pt-Ni alloy polyhedron nanochain catalyst, which is recorded as PtNi@PN-WC@CC.
[0021] The beneficial effects of the present invention are:
[0022] 1. Nitrogen-doped tungsten carbide nanoarrays grow on carbon cloth in the form of a ribbon structure. They have a high specific surface area and excellent acid and alkali resistance, and can be used as an excellent carrier. After plasma treatment, more active sites are exposed on the surface, which is more conducive to the subsequent loading of precious metals.
[0023] 2. The loaded Pt-Ni alloy polyhedron nanochains retain the structural advantages of nanopolyhedrons and nanowires, effectively alleviating the size effect. The nanowires have abundant atomic interfaces and Pt-rich surfaces, which can significantly increase the number of active centers.
[0024] 3. After loading Pt-Ni alloy polyhedron nanochains on the surface of the carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays, a second PECVD treatment was performed to further increase the number of active centers to improve the MOR performance.
[0025] 4. Platinum is doped with nickel to improve its resistance to CO poisoning, while tungsten carbide is considered to be completely immune to CO. The combination of the two further improves its resistance to CO poisoning. Since the high surface area of nitrogen-doped tungsten carbide improves the utilization efficiency of metal atoms, it exhibits excellent MOR and ORR performance and is used as a bifunctional catalyst for direct methanol fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The microscopic morphology of N-WC@CC prepared in Example 1 under a scanning electron microscope (SEM) (scale bar 3 μm);
[0027] Figure 2 Linear sweep voltammetry test diagram (LSV) of oxygen reduction reaction (ORR) of Examples 1, 2, 3 and Comparative Examples 1, 2;
[0028] Figure 3 The linear sweep voltammetry test diagram (LSV) of methanol oxidation reaction (MOR) of Examples 1, 2, 3 and Comparative Examples 1 and 2;
[0029] 1. PtNi@P-NWC@CC, 2. P-PtNi@PN-WC@CC-25, 3. P-PtNi@PN-WC@CC-100, 4. P-PtNi@PN-WC@CC-200, 5. P-PtNI@PN-WC@CC-300. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and beneficial technical effects of the present invention clearer, the beneficial effects of a direct methanol fuel cell bifunctional catalyst and a preparation method thereof of the present invention are described in detail below in combination with specific embodiments. The embodiments in this specification are only for explaining the present invention, not for limiting the present invention, and the parameters, proportions, etc. of the embodiments are selected according to actual conditions and have no substantial effect on the results.
[0031] The Ar / NH3 plasma modified nitrogen-doped tungsten carbide array surface-loaded Pt-Ni alloy polyhedron nanochain catalyst of the present invention uses carbon cloth loaded with nitrogen-doped carbon tungsten carbide nanoarray as a conductive substrate, and the platinum-nickel alloy nanochain is wound on the high-conductivity tungsten carbide substrate.
[0032] The specific preparation method comprises the following steps:
[0033] (i) Preparation of carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays;
[0034] (ii) surface treatment of carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays by PECVD to increase surface defects and improve substrate hydrophilicity;
[0035] (iii) Synthesis of Pt-Ni alloy polyhedral nanochains by hydrothermal reaction;
[0036] (iv) loading the synthesized Pt-Ni alloy polyhedron nanochains on the carbon cloth of nitrogen-doped tungsten carbide nanoarrays by self-adsorption;
[0037] (V) In order to remove the surfactant, the carbon cloth surface is calcined in air, nitrogen and argon hydrogen and then annealed to obtain a Pt-Ni alloy polyhedron nanochain catalyst loaded on the surface of the carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays.
[0038] (VI) The second PECVD treatment obtained the final sample Ar / NH3 plasma modified nitrogen-doped tungsten carbide array surface loaded with Pt-Ni alloy polyhedron nanochain catalyst. The actual preparation process of the four samples listed was used as a reference, and the corresponding bifunctional catalytic performance was tested to evaluate its use as a bifunctional catalyst for direct methanol fuel cells.
[0039] Embodiment 1:
[0040] A method for preparing a bifunctional catalyst for a direct methanol fuel cell comprises the following steps:
[0041] (I) Preparation of nitrogen-doped tungsten carbide array (N-WC@CC) using tungstic acid (H2WO4), hydrogen peroxide (H2O2) and carbon cloth (CC) as raw materials: WO3 nanoarray was prepared on CC by hydrothermal method. Tungstic acid powder (1.25g) was dissolved in 40ml 12wt% hydrogen peroxide under magnetic stirring, and the hydrogen peroxide solution was heated at 95℃ for 3h. Then 230μl HCl and 0.4g Na2SO4 were added and dissolved, and then put into the reactor and 2.5*2.5cm carbon was placed in it and heated at 180℃ for 12h to obtain WO3 nanoarray. Then 1.5g melamine was added and heated at 850℃ for 3h under argon for carbonization to obtain nitrogen-doped tungsten carbide array, recorded as N-WC@CC.
[0042] (ii) Surface treatment of nitrogen-doped tungsten carbide array: The substrate was subjected to room temperature plasma enhanced chemical vapor deposition in an Ar / NH3 (7%) atmosphere, with a gas flow rate of 20 Pa and a plasma discharge RF power of 100 W for 60 min, denoted as PN-WC@CC.
[0043] (III) Preparation of Pt-Ni alloy polyhedral nanochains: 0.075mmol Pt(acac)2, 0.0375mmol Ni(acac)2, 0.15mmol hexadecyltrimethylammonium chloride (CTAC), 0.75mmol glucose and 33mL oleylamine (Oam) were added to a beaker. The mixture was ultrasonically treated at room temperature for about 1.5h to form a uniformly distributed mixed solution. The mixed solution was then transferred to a reactor and heated from room temperature to 180°C and maintained at this temperature for 12h to complete the reaction. Thereafter, the product was naturally cooled to room temperature. The product was collected by centrifugation and washed with ethanol, and then dispersed in 15mL cyclohexane. The synthesized product was recorded as Pt-Ni PNC.
[0044] (iv) Preparation of platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material: The nitrogen-doped tungsten carbide array after plasma treatment was placed in 15 mL of cyclohexane and magnetically stirred for 15 min. At the same time, the prepared Pt-Ni alloy polyhedron nanochain was ultrasonically dispersed in another 15 mL of cyclohexane for 15 min. The two solutions were then mixed and dispersed and adsorbed under magnetic stirring for 12 h.
[0045] (V) Annealing after calcination of the platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material: Use an ordinary quartz tube furnace to place the dried platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material at the bottom of a ceramic boat, and raise the temperature from room temperature to calcination temperature 1 within 20 minutes under air. The calcination temperature 1 is 180°C and kept for 1 hour. Then, nitrogen is introduced into the tube furnace below the calcination temperature and kept for 2 hours. The heating rate from calcination temperature 1 to calcination temperature 2 is 7-8°C / min, and the calcination temperature 2 is 400°C and kept for 4 hours. The atmosphere is argon and hydrogen. The product is recorded as PtNi@PN-WC@CC.
[0046] (VI) Second plasma treatment: PtNi@PN-WC@CC was placed at the bottom of a ceramic boat after cooling by PECVD. Under an argon-ammonia atmosphere, the gas flow rate reached 30 Pa, the plasma discharge RF power was 75 W, and the treatment lasted for 60 min at a treatment temperature of 100 ° C. After cooling, the final sample was obtained, which was recorded as P-PtNi@PN-WC@CC-100.
[0047] The morphology of the N-WC@CC sample obtained in Example 1 was analyzed by scanning electron microscopy (SEM). Figure 1 The sample shown is a ribbon-shaped nanoarray uniformly grown on carbon cloth.
[0048] Bifunctional catalytic performance evaluation:
[0049] The electrocatalytic performance of the prepared samples was carried out in a three-electrode apparatus using an electrochemical workstation (CHI760E).
[0050] Preparation of working electrode for MOR and ORR performance test: Before using the rotating disk electrode (RDE), the glassy carbon electrode (GCE, d = 4.5 mm) was polished to a mirror surface with a polishing cloth containing Al2O3 powder, then rinsed with distilled water, dried at room temperature and used. The cut catalyst with a diameter of 4.5 mm was pasted on the surface of the GC electrode with Nafion solution (5wt.%), dried at room temperature, and used as the working electrode. Electrochemical performance test: During the test, a standard three-electrode electrochemical test system was used, in which the counter electrode was a Pt sheet electrode, the reference electrode was a saturated calomel electrode (SCE) and the working electrode prepared above. For the MOR test: the test solution was 0.5M H2SO4 + 1M CH3OH solution; for the ORR test: the test solution was 0.5M H2SO4. All potentials were calculated by referring to the reversible hydrogen electrode (RHE) through the Nernst equation: E(RHE) = E(Hg / Hg2Cl2) + 0.2415 + 0.059pH. Before the linear sweep voltammetry (LSV) test, the working electrode was charged at 10 mVs -1 The samples were activated by cyclic voltammetry (CV) for 50 cycles at a scan rate of 1.3 Å. All electrochemical tests were performed at room temperature.
[0051] The LSV curve of ORR of PtNi@PN-WC@CC-100 sample was tested in 0.5M H2SO4 solution saturated with O2 at a rotation speed of 1600rpm using a rotating disk electrode (RDE). Figure 2 shown.
[0052] The LSV curve of PtNi@PN-WC@CC-100 sample in 0.5M H2SO4+1MCH3OH solution MOR was tested by rotating disk electrode (RDE). Figure 3 shown.
[0053] Embodiment 2:
[0054] A method for preparing a bifunctional catalyst for a direct methanol fuel cell comprises the following steps:
[0055] (I) Preparation of nitrogen-doped tungsten carbide array (N-WC@CC) using tungstic acid (H2WO4), hydrogen peroxide (H2O2) and carbon cloth (CC) as raw materials: WO3 nanoarray was prepared on CC by hydrothermal method. Tungstic acid powder (1.25g) was dissolved in 40ml 12wt% hydrogen peroxide under magnetic stirring, and the hydrogen peroxide solution was heated at 95℃ for 3h. Then 230μl HCl and 0.4g Na2SO4 were added and dissolved, and then put into the reactor and 2.5*2.5cm carbon was placed in it and heated at 180℃ for 12h to obtain WO3 nanoarray. Then 1.5g melamine was added and heated at 850℃ for 3h under argon for carbonization to obtain nitrogen-doped tungsten carbide array, recorded as N-WC@CC.
[0056] (ii) Surface treatment of nitrogen-doped tungsten carbide array: The substrate was subjected to room temperature plasma enhanced chemical vapor deposition in an Ar / NH3 (7%) atmosphere, with a gas flow rate of 20 Pa and a plasma discharge RF power of 100 W for 60 min, denoted as PN-WC@CC.
[0057] (III) Preparation of Pt-Ni alloy polyhedral nanochains: 0.075mmol Pt(acac)2, 0.0375mmol Ni(acac)2, 0.15mmol hexadecyltrimethylammonium chloride (CTAC), 0.75mmol glucose and 33mL oleylamine (Oam) were added to a beaker. The mixture was ultrasonically treated at room temperature for about 1.5h to form a uniformly distributed mixed solution. The mixed solution was then transferred to a reactor and heated from room temperature to 180°C and maintained at this temperature for 12h to complete the reaction. Thereafter, the product was naturally cooled to room temperature. The product was collected by centrifugation and washed with ethanol, and then dispersed in 15mL cyclohexane. The synthesized product was recorded as Pt-Ni PNC.
[0058] (iv) Preparation of platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material: The nitrogen-doped tungsten carbide array after plasma treatment was placed in 15 mL of cyclohexane and magnetically stirred for 15 min. At the same time, the prepared Pt-Ni alloy polyhedron nanochain was ultrasonically dispersed in another 15 mL of cyclohexane for 15 min. The two solutions were then mixed and dispersed and adsorbed under magnetic stirring for 12 h.
[0059] (V) Annealing after calcination of the platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material: Use an ordinary quartz tube furnace to place the dried platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material at the bottom of a ceramic boat, and raise the temperature from room temperature to calcination temperature 1 within 20 minutes under air. The calcination temperature 1 is 180°C and kept for 1 hour. Then, nitrogen is introduced into the tube furnace below the calcination temperature and kept for 2 hours. The heating rate from calcination temperature 1 to calcination temperature 2 is 7-8°C / min, and the calcination temperature 2 is 400°C and kept for 4 hours. The atmosphere is argon and hydrogen. The product is recorded as PtNi@PN-WC@CC.
[0060] (VI) Secondary plasma treatment: PtNi@PN-WC@CC was placed at the bottom of a ceramic boat after cooling by PECVD. Under an argon-ammonia atmosphere, the gas flow rate reached 30 Pa, the plasma discharge RF power was 75 W, and the treatment temperature was 200 degrees Celsius for 60 minutes. After cooling, the final sample was obtained, which was recorded as P-PtNi@PN-WC@CC-200.
[0061] Bifunctional catalytic performance evaluation:
[0062] The LSV curve of ORR of PtNi@PN-WC@CC-200 sample was tested in 0.5M H2SO4 solution saturated with O2 at a rotation speed of 1600rpm using a rotating disk electrode (RDE). Figure 2 shown.
[0063] The LSV curve of PtNi@PN-WC@CC-200 sample in 0.5M H2SO4+1MCH3OH solution MOR was tested by rotating disk electrode (RDE). Figure 3 shown.
[0064] Embodiment 3:
[0065] A method for preparing a bifunctional catalyst for a direct methanol fuel cell comprises the following steps:
[0066] (I) Preparation of nitrogen-doped tungsten carbide array (N-WC@CC) using tungstic acid (H2WO4), hydrogen peroxide (H2O2) and carbon cloth (CC) as raw materials: WO3 nanoarray was prepared on CC by hydrothermal method. Tungstic acid powder (1.25g) was dissolved in 40ml 12wt% hydrogen peroxide under magnetic stirring, and the hydrogen peroxide solution was heated at 95℃ for 3h. Then 230μl HCl and 0.4g Na2SO4 were added and dissolved, and then put into the reactor and 2.5*2.5cm carbon was placed in it and heated at 180℃ for 12h to obtain WO3 nanoarray. Then 1.5g melamine was added and heated at 850℃ for 3h under argon for carbonization to obtain nitrogen-doped tungsten carbide array, recorded as N-WC@CC.
[0067] (ii) Surface treatment of nitrogen-doped tungsten carbide array: The substrate was subjected to room temperature plasma enhanced chemical vapor deposition in an Ar / NH3 (7%) atmosphere, with a gas flow rate of 20 Pa and a plasma discharge RF power of 100 W for 60 min, denoted as PN-WC@CC.
[0068] (III) Preparation of Pt-Ni alloy polyhedral nanochains: 0.075mmol Pt(acac)2, 0.0375mmol Ni(acac)2, 0.15mmol hexadecyltrimethylammonium chloride (CTAC), 0.75mmol glucose and 33mL oleylamine (Oam) were added to a beaker. The mixture was ultrasonically treated at room temperature for about 1.5h to form a uniformly distributed mixed solution. The mixed solution was then transferred to a reactor and heated from room temperature to 180°C and maintained at this temperature for 12h to complete the reaction. Thereafter, the product was naturally cooled to room temperature. The product was collected by centrifugation and washed with ethanol, and then dispersed in 15mL cyclohexane. The synthesized product was recorded as Pt-Ni PNC.
[0069] (iv) Preparation of platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material: The nitrogen-doped tungsten carbide array after plasma treatment was placed in 15 mL of cyclohexane and magnetically stirred for 15 min. At the same time, the prepared Pt-Ni alloy polyhedron nanochain was ultrasonically dispersed in another 15 mL of cyclohexane for 15 min. The two solutions were then mixed and dispersed and adsorbed under magnetic stirring for 12 h.
[0070] (V) Annealing after calcination of the platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material: Use an ordinary quartz tube furnace to place the dried platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material at the bottom of a ceramic boat, and raise the temperature from room temperature to calcination temperature 1 within 20 minutes under air. The calcination temperature 1 is 180°C and kept for 1 hour. Then, nitrogen is introduced into the tube furnace below the calcination temperature and kept for 2 hours. The heating rate from calcination temperature 1 to calcination temperature 2 is 7-8°C / min, and the calcination temperature 2 is 400°C and kept for 4 hours. The atmosphere is argon and hydrogen. The product is recorded as PtNi@PN-WC@CC.
[0071] (VI) Secondary plasma treatment: PtNi@PN-WC@CC was placed at the bottom of a ceramic boat after cooling by PECVD. Under an argon-ammonia atmosphere, the gas flow rate reached 30 Pa, the plasma discharge RF power was 75 W, and the treatment temperature was 300 degrees Celsius for 60 minutes. After cooling, the final sample was obtained, which was recorded as P-PtNi@PN-WC@CC-300.
[0072] Bifunctional catalytic performance evaluation:
[0073] The LSV curve of ORR of PtNi@PN-WC@CC-300 sample was tested in 0.5M H2SO4 solution saturated with O2 at a rotation speed of 1600rpm using a rotating disk electrode (RDE). Figure 2 shown.
[0074] The LSV curve of PtNi@PN-WC@CC-300 sample in 0.5M H2SO4+1MCH3OH solution MOR was tested by rotating disk electrode (RDE). Figure 3 shown.
[0075] Comparative Example 1
[0076] A method for preparing a bifunctional catalyst for a direct methanol fuel cell comprises the following steps:
[0077] (I) Preparation of nitrogen-doped tungsten carbide array (N-WC@CC) using tungstic acid (H2WO4), hydrogen peroxide (H2O2) and carbon cloth (CC) as raw materials: WO3 nanoarray was prepared on CC by hydrothermal method. Tungstic acid powder (1.25g) was dissolved in 40ml 12wt% hydrogen peroxide under magnetic stirring, and the hydrogen peroxide solution was heated at 95℃ for 3h. Then 230μl HCl and 0.4g Na2SO4 were added and dissolved, and then put into the reactor and 2.5*2.5cm carbon was placed in it and heated at 180℃ for 12h to obtain WO3 nanoarray. Then 1.5g melamine was added and heated at 850℃ for 3h under argon for carbonization to obtain nitrogen-doped tungsten carbide array, recorded as N-WC@CC.
[0078] (ii) Surface treatment of nitrogen-doped tungsten carbide array: The substrate was subjected to room temperature plasma enhanced chemical vapor deposition in an Ar / NH3 (7%) atmosphere, with a gas flow rate of 20 Pa and a plasma discharge RF power of 100 W for 60 min, denoted as PN-WC@CC.
[0079] (III) Preparation of Pt-Ni alloy polyhedral nanochains: 0.075mmol Pt(acac)2, 0.0375mmol Ni(acac)2, 0.15mmol hexadecyltrimethylammonium chloride (CTAC), 0.75mmol glucose and 33mL oleylamine (Oam) were added to a beaker. The mixture was ultrasonically treated at room temperature for about 1.5h to form a uniformly distributed mixed solution. The mixed solution was then transferred to a reactor and heated from room temperature to 180°C and maintained at this temperature for 12h to complete the reaction. Thereafter, the product was naturally cooled to room temperature. The product was collected by centrifugation and washed with ethanol, and then dispersed in 15mL cyclohexane. The synthesized product was recorded as Pt-Ni PNC.
[0080] (iv) Preparation of platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material: The nitrogen-doped tungsten carbide array after plasma treatment was placed in 15 mL of cyclohexane and magnetically stirred for 15 min. At the same time, the prepared Pt-Ni alloy polyhedron nanochain was ultrasonically dispersed in another 15 mL of cyclohexane for 15 min. The two solutions were then mixed and dispersed and adsorbed under magnetic stirring for 12 h.
[0081] (V) Annealing after calcination of the platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material: Use an ordinary quartz tube furnace to place the dried platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material at the bottom of a ceramic boat, and raise the temperature from room temperature to calcination temperature 1 within 20 minutes under air. The calcination temperature 1 is 180°C and kept for 1 hour. Then, nitrogen is introduced into the tube furnace below the calcination temperature and kept for 2 hours. The heating rate from calcination temperature 1 to calcination temperature 2 is 7-8°C / min, and the calcination temperature 2 is 400°C and kept for 4 hours. The atmosphere is argon and hydrogen. The product is recorded as PtNi@PN-WC@CC.
[0082] Bifunctional catalytic performance evaluation:
[0083] The LSV curve of ORR of PtNi@PN-WC@CC sample was tested in 0.5M H2SO4 solution saturated with O2 at a rotation speed of 1600rpm using a rotating disk electrode (RDE). Figure 2 shown.
[0084] The LSV curve of the PtNi@PN-WC@CC sample in 0.5M H2SO4+1M CH3OH solution MOR was tested by rotating disk electrode (RDE). Figure 3 shown.
[0085] Comparative Example 2
[0086] A method for preparing a bifunctional catalyst for a direct methanol fuel cell comprises the following steps:
[0087] (I) Preparation of nitrogen-doped tungsten carbide array (N-WC@CC) using tungstic acid (H2WO4), hydrogen peroxide (H2O2) and carbon cloth (CC) as raw materials: WO3 nanoarray was prepared on CC by hydrothermal method. Tungstic acid powder (1.25g) was dissolved in 40ml 12wt% hydrogen peroxide under magnetic stirring, and the hydrogen peroxide solution was heated at 95℃ for 3h. Then 230μl HCl and 0.4g Na2SO4 were added and dissolved, and then put into the reactor and 2.5*2.5cm carbon was placed in it and heated at 180℃ for 12h to obtain WO3 nanoarray. Then 1.5g melamine was added and heated at 850℃ for 3h under argon for carbonization to obtain nitrogen-doped tungsten carbide array, recorded as N-WC@CC.
[0088] (ii) Surface treatment of nitrogen-doped tungsten carbide array: The substrate was subjected to room temperature plasma enhanced chemical vapor deposition in an Ar / NH3 (7%) atmosphere, with a gas flow rate of 20 Pa and a plasma discharge RF power of 100 W for 60 min, denoted as PN-WC@CC.
[0089] (III) Preparation of Pt-Ni alloy polyhedral nanochains: 0.075mmol Pt(acac)2, 0.0375mmol Ni(acac)2, 0.15mmol hexadecyltrimethylammonium chloride (CTAC), 0.75mmol glucose and 33mL oleylamine (Oam) were added to a beaker. The mixture was ultrasonically treated at room temperature for about 1.5h to form a uniformly distributed mixed solution. The mixed solution was then transferred to a reactor and heated from room temperature to 180°C and maintained at this temperature for 12h to complete the reaction. Thereafter, the product was naturally cooled to room temperature. The product was collected by centrifugation and washed with ethanol, and then dispersed in 15mL cyclohexane. The synthesized product was recorded as Pt-Ni PNC.
[0090] (iv) Preparation of platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material: The nitrogen-doped tungsten carbide array after plasma treatment was placed in 15 mL of cyclohexane and magnetically stirred for 15 min. At the same time, the prepared Pt-Ni alloy polyhedron nanochain was ultrasonically dispersed in another 15 mL of cyclohexane for 15 min. The two solutions were then mixed and dispersed and adsorbed under magnetic stirring for 12 h.
[0091] (V) Annealing after calcination of the platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material: Use an ordinary quartz tube furnace to place the dried platinum-nickel alloy polyhedron nanochain @ tungsten carbide composite material at the bottom of a ceramic boat, and raise the temperature from room temperature to calcination temperature 1 within 20 minutes under air. The calcination temperature 1 is 180°C and kept for 1 hour. Then, nitrogen is introduced into the tube furnace below the calcination temperature and kept for 2 hours. The heating rate from calcination temperature 1 to calcination temperature 2 is 7-8°C / min, and the calcination temperature 2 is 400°C and kept for 4 hours. The atmosphere is argon and hydrogen. The product is recorded as PtNi@PN-WC@CC.
[0092] (VI) Secondary plasma treatment: PtNi@PN-WC@CC was placed at the bottom of a ceramic boat after cooling by PECVD. Under an argon-ammonia atmosphere, the gas flow rate reached 30 Pa, the plasma discharge RF power was 75 W, and the treatment temperature was 300 degrees Celsius for 60 minutes. After cooling, the final sample was obtained, which was recorded as P-PtNi@PN-WC@CC-25.
[0093] Bifunctional catalytic performance evaluation:
[0094] The LSV curve of ORR of PtNi@PN-WC@CC-25 sample was tested by rotating disk electrode (RDE) in 0.5M H2SO4 solution saturated with O2 at a rotation speed of 1600rpm. Figure 2 shown.
[0095] The LSV curve of the PtNi@PN-WC@CC-25 sample in 0.5M H2SO4+1M CH3OH solution MOR was tested by rotating disk electrode (RDE). Figure 3 shown.
[0096] like Figure 2 As shown, the product obtained in Example 1 is P-PtNi@PN-WC@CC-100. The product obtained in Example 2 is P-PtNi@PN-WC@CC-200. The product obtained in Comparative Example 1 is PtNi@PN-WC@CC. The product obtained in Comparative Example 2 is P-PtNi@PN-WC@CC-25. The product obtained in Comparative Example 3 is P-PtNi@PN-WC@CC-300.
[0097] The MOR catalytic activity is exactly the same as the ORR test. The LSV curve of the MOR catalytic performance is as follows: Figure 3 As shown. Under the same test conditions, the current density of the products prepared by the preparation processes described in Examples 1 and 2 of the present invention is significantly higher than that of Comparative Examples 1, 2 and 3. Among them, P-PtNi@PN-WC@CC-200 exhibits the highest current density. Therefore, the optimal treatment temperature for the second plasma treatment in step 6 is 200°C.
[0098] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A direct methanol fuel cell bifunctional catalyst, characterized in that: Carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays is used as a conductive substrate, and platinum-nickel alloy nanochains are wrapped around the highly conductive tungsten carbide substrate.
2. A method for preparing a bifunctional catalyst for a direct methanol fuel cell, characterized in that: The method comprises the following steps: (1) preparing a carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays; (2) Surface treatment of carbon cloth loaded with nitrogen-doped tungsten carbide nanoarrays by PECVD; (3) Synthesis of Pt-Ni alloy polyhedral nanochains by hydrothermal reaction; (4) The Pt-Ni alloy polyhedron nanochain synthesized in step 3 is loaded on the carbon cloth of the nitrogen-doped tungsten carbide nanoarray treated in step 2 by self-adsorption to obtain a platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material; (5) calcining the platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material obtained in step 4 in air, nitrogen and argon-hydrogen successively and then annealing to obtain a carbon cloth surface loaded with nitrogen-doped tungsten carbide nanoarrays and loaded with a Pt-Ni alloy polyhedron nanochain catalyst; (6) A second PECVD treatment is performed to obtain a Pt-Ni alloy polyhedral nanochain catalyst loaded on the surface of a nitrogen-doped tungsten carbide array modified by Ar / NH3 plasma, which is a bifunctional catalyst for direct methanol fuel cells.
3. The method for preparing a bifunctional catalyst for a direct methanol fuel cell according to claim 2, characterized in that: The treatment temperature of the second PECVD treatment in step 6 is 100-300°C.
4. The method for preparing a bifunctional catalyst for a direct methanol fuel cell according to claim 2, characterized in that: Step 6 includes: cooling the carbon cloth surface loaded with nitrogen-doped tungsten carbide nanoarray obtained in step 5 and then subjecting it to a second PECVD treatment, the atmosphere is argon ammonia, the gas flow rate is 30Pa, the plasma discharge RF power is 75W, the duration is 60min, the treatment temperature is 200°C, and after cooling, Ar / NH3 plasma modified nitrogen-doped tungsten carbide array surface loaded with Pt-Ni alloy polyhedron nanochain catalyst is obtained, recorded as P-PtNi@PN-WC@CC.
5. The method for preparing a bifunctional catalyst for a direct methanol fuel cell according to claim 2, characterized in that: Step 1 comprises: dissolving tungstic acid powder in hydrogen peroxide, heating at 90-100°C for 2.5-3.5h, then adding HCl and Na2SO4 to dissolve, placing carbon therein and heating at 170-180°C for 11-13h to obtain a WO3 nanoarray, then adding melamine and heating at 800-900°C under argon for 2.5-3.5h for carbonization to obtain a nitrogen-doped tungsten carbide array.
6. The method for preparing a bifunctional catalyst for a direct methanol fuel cell according to claim 2, characterized in that: Step 2 includes: performing room temperature plasma enhanced chemical vapor deposition on the substrate in an Ar / NH3 atmosphere, with a gas flow rate of 18-22Pa and a plasma discharge radio frequency power supply power of 95-105W for 50-70 minutes.
7. The method for preparing a bifunctional catalyst for a direct methanol fuel cell according to claim 2, characterized in that: Step 3 comprises: mixing a platinum source, a nickel source, hexadecyltrimethylammonium chloride, glucose and oleylamine, ultrasonically treating the mixture at room temperature to form a uniformly distributed mixed solution, then heating from room temperature to 170-190° C. and maintaining the temperature for 11-13 hours to complete the reaction, naturally cooling the product to room temperature, collecting the product by centrifugation and washing it with ethanol to obtain a Pt-Ni alloy polyhedral nanochain.
8. The method for preparing a bifunctional catalyst for a direct methanol fuel cell according to claim 5, characterized in that: The platinum source is platinum acetylacetonate, the nickel source is nickel acetylacetonate, and the molar ratio of platinum acetylacetonate to nickel acetylacetonate is 2:
1.
9. The method for preparing a bifunctional catalyst for a direct methanol fuel cell according to claim 2, characterized in that: Step 4 includes: placing the nitrogen-doped tungsten carbide array treated in step 2 into cyclohexane, magnetically stirring, ultrasonically dispersing the Pt-Ni alloy polyhedron nanochain prepared in step 3 in another portion of cyclohexane, and then mixing the above two solutions, and then magnetically stirring and dispersing and adsorbing for 12 hours to obtain a platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material.
10. The method for preparing a bifunctional catalyst for a direct methanol fuel cell according to claim 2, characterized in that: Step 5 includes: the platinum-nickel alloy polyhedron nanochain@tungsten carbide composite material obtained in step 4 is heated from room temperature to 180°C in air within 20 minutes, and kept warm for 1 hour; nitrogen is introduced and kept warm for 2 hours; and then the temperature is raised to 400°C at a rate of 7-8°C / min in an argon-hydrogen atmosphere, and kept warm for 4 hours to obtain a carbon cloth surface loaded with nitrogen-doped tungsten carbide nanoarrays, which is a Pt-Ni alloy polyhedron nanochain catalyst, recorded as PtNi@PN-WC@CC.
Citation Information
Patent Citations
Method for preparing anatase titanium dioxide nanoribbon array membrane
CN104032292A
Tungsten carbide nano-array material and preparation method and application thereof
CN108203095A
Preparation method of plasma-based supported noble metal catalyst
CN112246288A
PtNi polyhedral nanochain, preparation method thereof and application
CN113843413A
Method for electrocatalytic oxidation of sulfur dioxide by tungsten carbide nano array electrode and application
CN115233251A
